2016
DOI: 10.1016/j.bcp.2016.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Free-fatty acid receptor-4 (GPR120): Cellular and molecular function and its role in metabolic disorders

Abstract: Over the last decade, a subfamily of G protein-coupled receptors that are agonized by endogenous and dietary free-fatty acids (FFA) has been discovered. These free-fatty acid receptors include FFA2 and FFA3, which are agonized by short-chained FFA, as well as FFA1 and FFA4, which are agonized by medium-to-long chained FFA. Ligands for FFA1 and FFA4 comprise the family of long chain polyunsaturated omega-3 fatty acids including α-linolenic acid (ALA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 79 publications
1
70
0
3
Order By: Relevance
“…Due to its more ubiquitous expression, much more work has been published on the shorter FFA4 isoform (12), while very little has been described regarding the function of FFA4-L. A study published in 2012 showed that agonism of FFA4-S transiently expressed in HEK-293 cells could signal via both Gαq/11 and β-arrestin-2 cascades, while importantly, agonism of FFA-L was incapable of promoting Ca 2+ -dependent signals via Gαq/11, yet could signal fully via β-arrestin-2 (17). Our results shed further light on differences in signal capabilities of the two FFA4 isoforms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its more ubiquitous expression, much more work has been published on the shorter FFA4 isoform (12), while very little has been described regarding the function of FFA4-L. A study published in 2012 showed that agonism of FFA4-S transiently expressed in HEK-293 cells could signal via both Gαq/11 and β-arrestin-2 cascades, while importantly, agonism of FFA-L was incapable of promoting Ca 2+ -dependent signals via Gαq/11, yet could signal fully via β-arrestin-2 (17). Our results shed further light on differences in signal capabilities of the two FFA4 isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…These free-fatty acid receptors include FFA2 and FFA3, which are agonized by short-chained FFA, as well as FFA1 and FFA4, which are agonized by medium-to-long chained FFA. FFA4, previously termed GPR120, has recently drawn considerable attention due to its profound anti-inflammatory effects (reviewed in 12). Oh and colleagues recently demonstrated that FFA4 agonism can reverse LPS-induced activation of NF-κB and inhibit release of proinflammatory IL-6 and TNF–α from macrophages, in a manner dependent on interaction with β-arrestin-2 partner proteins (13).…”
Section: Introductionmentioning
confidence: 99%
“…This concept of the molecular mode of action of ω3‐PUFAs has been extended by another putatively most important mechanism since DHA and EPA were identified as cognate ligands of the G protein‐coupled receptor (GPCR) 120. GPR120 was deorphanized in 2005 to bind the ω3‐PUFAs docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA), and α‐linolenic acid as well as palmitoleic, myristic, and linoleic acid as agonistic, cognate ligands . It was subsequently renamed Free Fatty Acid receptor 4 (FFA4) by the International Union of Basic and Clinical Pharmacology .…”
Section: Introductionmentioning
confidence: 99%
“…To date, most extensively investigated physiological role of GPR120/FFA4 is its positive effect on insulin sensitivity, which has sparked broad interest into the development of GPR120/FFA4 agonists as novel antidiabetics . In recent years, it has been shown that FFA4 is also expressed on immune cells, including monocytes/macrophages, dendritic cells, and eosinophils, suggesting that GPR120/FFA4 may mediate immunomodulatory actions of ω3‐PUFAs. In line with this notion, in vitro activation of GPR120/FFA4 in macrophages curbs their immune response to NLPR3 inflammasome, TLR4, or TNF‐α activation, and in vivo GPR120 is required for ω3‐PUFAs to counteract adipose tissue inflammation induced by high‐fat diet in mice by limiting the recruitment of monocyte/macrophages into adipose and reducing the release of proinflammatory M1 macrophage‐derived immunomediators, such as IL‐1β, TNF‐α, MCP‐1, and IL‐6, while in parallel promoting the expression of antiinflammatory M2 macrophages, such as IL‐10, arginase 1, Ym‐1, and Clec7a .…”
Section: Introductionmentioning
confidence: 99%
“…Among these potential targets, FFAR1 and FFAR4 are the most closely related to the regulation of glucose‐stimulated insulin secretion (GSIS) and other regulatory processes associated with T2DM. Readers interested in the pharmacology of FFARs may also refer to several comprehensive reviews . Of particular interest is FFAR1, which plays a key role in stimulating the release of incretins on enteroendocrine cells and amplifying GSIS on pancreatic β‐cells, suggesting that FFAR1 might be a promising antidiabetic target associated with low risk of hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%